The Position of the Principle of Legality vs the Principle of Opportunity in the Accemination of the Prosecutor's Demands in the Replic Agenda (Valencya Case Study at the Karawang State Attorney) - Sitompul, Rina Melati; Pasaribu, Juniarti Canceria (Universitas Sumatera Utara, 2024)
Withdrawing criminal charges against Valencya during a trial's replication stage has generated debate, seemingly balancing the principles of legality and opportunity. This issue is significant because the Prosecutor in the Valencya Case has effectively assumed the role of Legal Advisor. This study presents a descriptive analysis of normative research within the criminal procedure system. By detailing the placement of legal charges in the Valencya case, a thorough analysis is conducted regarding the Public Prosecutor's authority in determining the legality and the discretion to discontinue prosecution. The Principle of Opportunity justifies discontinuation efforts in charge acquisition, even when clearance requirements are conducted in the replica agenda. While prioritizing legal interests to achieve justice for victims, the principle of legality can be waived, aligning with the concept of restorative justice in the Prosecutor's Office agenda.